2021
DOI: 10.1177/03008916211026977
|View full text |Cite
|
Sign up to set email alerts
|

Occult lymph node metastasis in patients with laryngeal cancer and relevant predicting factors: a single-center experience

Abstract: Objective: To reveal the incidence and predictive parameters of occult cervical lymph node metastasis (LNM) in patients with cN0 laryngeal squamous cell cancer (LSCC) who underwent surgery as definitive treatment. Methods: Patients with cN0 laryngeal cancer who had undergone elective neck dissection together with partial or total laryngectomy between January 2006 and November 2020 were retrospectively analyzed. Clinical and histopathologic predictors of occult metastasis were also analyzed. Follow-up data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…found a very low incidence of LNM in T1-T2 stage and well-differentiated tumors. These data suggested that a watchful waiting strategy can be used in T1-T2 and selected T3 cases with well-differentiated tumors ( 6 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…found a very low incidence of LNM in T1-T2 stage and well-differentiated tumors. These data suggested that a watchful waiting strategy can be used in T1-T2 and selected T3 cases with well-differentiated tumors ( 6 ).…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have identified indicators that may be independent factors for LNM such as the tumor depth, the degree of tumor differentiation, T-stage, thyroid cartilage invasion, and extra laryngeal extension. Traditional methods for determining the factors related to LNM are largely qualitative and there remains a need to develop quantitative measures to assess the factors associated with the risk of LNM ( 6 , 7 ). The accurate preoperative evaluation of LNM risk may guide the use of optimized treatment strategies in patients with supraglottic LSCC and provide important prognostic information.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the presence of LNM is mainly determined by cervical palpation and preoperative imaging, which largely depend on the clinical experience of the doctor and the ability of the human eye to identify imaging [21,22]. As reported, the presence of occult metastasis was confrmed by postsurgery histological examination in 4%-40% of cN0 LC patients [23][24][25]. Although prophylactic cervical LND can decrease the risk of LNM [26], it puts LC patients at a higher risk for operations, such as major bleeds, lymphatic fstulas, or impairments in the vagus, brachial plexus, and recurrent laryngeal nerve [27].…”
Section: Discussionmentioning
confidence: 97%
“…However, a study by Sessions et al found that patients with N0 disease may be safely observed with no loss of survival advantage [ 44 ]. Furthermore, Ömer et al showed that a watchful waiting strategy can be applied to T1-T2 and selected T3 cases with well-differentiated tumours [ 23 ]. These data further suggested that the LNM of LC is influenced by several factors, and that it is not accurate to judge LNM solely by T-stage and primary site.…”
Section: Discussionmentioning
confidence: 99%
“…LSCC, especially poorly differentiated LSCC, is associated with high degree of malignancy, showing high potential of metastasis, leading to the low postoperative survival rate. Lymph node metastasis has been previously shown closely related to the prognosis of LSCC (Bayir et al 2021 ). Therefore, understanding the pathogenesis of LSCC, especially the molecular mechanism contributing to the metastasis, is beneficial to the early diagnosis and treatment of this disease (Olsen 2010 ; Rudolph et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%